Performance estimation of a steam-turbine driven multistage compressor system - Aleksa Miladinović; Jasna Stajić – Trošić; Mirjana Kijevčanin; Vladimir Stijepović; Sabla Y. Alnouri; Mirko Stijepović (Case Studies in Thermal Engineering)
This work presents a deterministic model developed to estimate the real-time performance parameters of a compact device which uses a steam turbine to drive a multistage compressor system. The approach focuses on evaluating the thermal and mechanical efficiencies of individual system components, including steam turbines and multistage compressors under varying operating conditions, with particular attention to system-level energy efficiency and interdependencies. The model captures the interaction between the steam turbines and compressors, enabling an integrated analysis of energy transfer, shaft power consumption, and thermodynamic and mechanical losses across system. A case study was conducted on three steam-driven multistage compressor system (SDMSCS) units at a local ethylene plant: Case 1 (cracked gas), and Case 2 (propylene), Case 3 (ethylene), so as to demonstrate the effectiveness and versatility of the proposed method. The model was validated by comparing simulated results to actual energy consumption data, and design specifications were used as a reference point. The analysis estimated energy transfer per compressor stage, turbine-extracted energy, shaft power, polytropic efficiency, and mechanical efficiency. It was found that Case 2 exhibits the highest model accuracy with close alignment to design efficiencies across stages, while Case 1 resulted in significant underprediction and larger deviations, especially in later stages. As such, the method's effectiveness was demonstrated with model efficiencies closely matching design values within 2–10 % deviation for most stages, and highlighting areas for improvement where deviations reached up to 37 % in later stages.